2017
DOI: 10.1002/slct.201700708
|View full text |Cite
|
Sign up to set email alerts
|

Dramatically Enhanced Phenol Degradation on Alkali Cation‐Anchored TiO2/SiO2 Hybrids: Effect of Cation‐π Interaction as a Diffusion‐Controlling Tool in Heterogeneous Catalysis

Abstract: Cation‐π interaction is an intermolecular interaction between the face of a π system and an adjacent cation, which brings about a change in molecular dynamics of organic reactants in catalysis. In this study, a series of alkali metal cations‐anchored TiO2/SiO2 hybrid catalysts were prepared based on organo‐functionalized MCM‐41 mesoporous silica, in order to examine the effect of cation‐π interaction in heterogeneous catalysis. Immobilizing heavier alkali metal cations on surface‐functionalized carboxylic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Recently, the authors found that a series of alkali metal cation-anchored TiO 2 /SiO 2 hybrid catalysts significantly enhanced the degradation of phenol under UV irradiation, suggesting that a cation−π interaction acts as a diffusioncontrolling tool in such reaction systems. 442 4.2.2. Photochemical Reactions.…”
Section: Reactions In Zeolitesmentioning
confidence: 99%
“…Recently, the authors found that a series of alkali metal cation-anchored TiO 2 /SiO 2 hybrid catalysts significantly enhanced the degradation of phenol under UV irradiation, suggesting that a cation−π interaction acts as a diffusioncontrolling tool in such reaction systems. 442 4.2.2. Photochemical Reactions.…”
Section: Reactions In Zeolitesmentioning
confidence: 99%
“…In 2017, Yamashita et al [124], prepared TiO 2 /MCM-41 catalyst with alkali metal cations embebed (Li + , Na + , K + , Rb + , Cs + ) within its pores. In this regard, a previous post-modification of the MCM-41 with carboxylic acid groups was needed.…”
Section: Titanium Nanoparticles Supported On Mcm-41mentioning
confidence: 99%
“…Schematic illustration of alkali metal cations-anchored mesoporous silica with catalytic centres. Reproduced with permission from[124]. Copyright 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
mentioning
confidence: 99%